IDENTIFIKASI KOMODITAS UNGGULAN PERTANIAN UNTUK PENGEMBANGAN EKONOMI DAERAH TERTINGGAL DI KABUPATEN SUMBAWA BARAT - Binar Dwiyanto Pamungkas; A Asmini; Muhammad Kevin (Pusat Riset dan Publikasi, 2022)
This study aims to determine the leading agricultural commodities found in each sub-district that is lagging behind in West Sumbawa Regency. This type of research is descriptive, the analytical tool used to solve the problem in this research is Location Quotient (LQ) analysis. The results of the Location Quotient (LQ) analysis show that the most superior agricultural commodities in economically disadvantaged sub-districts in West Sumbawa Regency consist of three agricultural commodities, namely: rice, corn, and cattle.